Pemanfaatan Limbah Organik Rumah Tangga sebagai Bahan Baku Pembuatan Biogas Ramah Lingkungan - Marlita Kenny Saraswati; Elsa Rosyidah (Jurnal Teknik dan Teknologi Indonesia, 2024)
Household organic waste is one of the largest contributors to municipal solid waste in Indonesia and, if not properly managed, can cause significant environmental pollution. The utilization of organic waste through anaerobic digestion to produce biogas offers an environmentally friendly solution while simultaneously providing a renewable energy source. This study aims to analyze the potential of biogas production from household organic waste and to evaluate the quality of the resulting biogas. The methodology includes collecting household organic waste samples, conducting fermentation in a laboratory-scale digester, and measuring the volume and methane content of the produced biogas. The results indicate that household organic waste, particularly food residues, contains a high level of organic matter, enabling significant biogas generation with methane concentrations suitable for alternative fuel use. The utilization of household organic waste for biogas production not only supports waste reduction efforts but also contributes to the development of clean and sustainable energy.